3D micromechanical simulation of the mechanical behavior of an in-situ Al3Ti/A356 composite. (1st November 2019) - Ma, Siming; Zhuang, Xincun; Wang, Xiaoming
Abstract: The mechanical behavior of an in-situ Al3 Ti/A356 composite was studied by three-dimensional (3D) micromechanical simulation with microstructure-based Representative Volume Element (RVE) models. A series of 3D RVEs were automatically generated with A356 matrix and icosahedron shaped Al3 Ti particles as representative of various microstructures. Ductile damage of matrix and brittle damage of Al3 Ti particles were considered, while perfect interfacial bonding between Al3 Ti and Al matrix was assumed. Simulation results were validated by experimental stress-strain curves. Furthermore, the effects of the particle size, volume fraction and distribution of Al3 Ti on mechanical properties were simulated by controlling the corresponding parameters in RVEs. The simulation results show that the refinement of particles improves the yield strength and elongation. However, the increase of volume fraction or clustering of the particles reduces the elongation evidently. Additionally, the Young's modulus, yield strength and elongation of the Al3 Ti/A356 composite were predicted from different RVE models. The prediction shows that the Young's modulus follows the calculation of Tsai-Halpin equation. The yield strengths are close to the micromechanical approach considering both load bearing and coefficient of thermal expansion (CTE) mismatch strengthening contribution. The relationship between elongation and the properties of the Al3 Ti particles is set up by a polynomial fitting, which is generally in agreement with reported experimental results. Graphical abstract: Image 1